Use of lipopolysaccharides to characterize Bradyrhizobium spp. - Carareto Alves, Lúcia M. [UNESP]; Lemos, Eliana G. M. [UNESP] (Elsevier, 1996)
Three methods of extraction of lipopolysaccharide (LPS) were compared-the conventional hot phenol-water method with 40% phenol, a modified form of this method using 10% phenol, and the hot saline method. Good recovery of LPS was achieved by each of the three methods, with the LPS found in the aqueous phase with the two phenol-based procedures. The application of SDS-PAGE to the LPS extracts, followed by silver staining, showed similar banding with all three methods of extraction. When the hot saline extraction LPS fraction from eight strains of Bradyrhizobium spp. and eight strains of Bradyrhizobium japonicum was compared with SDS-PAGE, characteristic profiles were achieved. Serological analysis of eight strains of Bradyrhizobium spp., using antisera prepared against whole cells in agglutination reactions, showed extensive sharing of antigens. When antisera was prepared using outer membrane LPS, extracted by the hot saline method, the amount of cross-reaction was reduced greatly. The results indicated that LPS provide an efficient means of obtaining monospecific antisera to be used for serological identification of strains of Bradyrhizobium spp. and that the hot saline extraction method is recommended for a fast, simple and efficient way to obtain LPS and characterize this bacterium.
Keywords: bacteria; lipopolysaccharide; method comparison; rhizobacteria; species identification; Bradyrhizobium; Bradyrhizobium japonicum